Prolactin Concentrations in Patients with Breast Cancer. Issue 5940 (9th November 1974) - Franks, S.; Ralphs, D. N. L.; Seagroatt, Valerie; Jacobs, H. S.
Abstract : Basal prolactin levels were measured before operation in 113 patients undergoing surgery for a lump in the breast. Prolactin concentrations were not significantly higher in those patients with breast cancer than in those with benign lumps. Prolactin concentrations were, however, found to be higher in premenopausal women than in postmenopausal ones, regardless of tumour histology.